The effect of smart app creator application on ımproving students' critical thinking - Shavab, Oka; Afriza, Edi; Jayusman, Iyus (Harmoni Sosial: Jurnal Pendidikan IPS, 2025)
This study aims to evaluate the extent to which students' critical thinking skills are improved by the utilization of the smart apps creator program. A quasi-experimental research methodology utilizing a nonequivalent control group design is applied. Purposive sampling was used to choose 150 students for the research sample. A multiple-choice exam was used to gather data. The Mann-Whitney U Test and descriptive statistics were used to analyze the data. The n-gain value for the experimental class was 0.7629, whereas that of the control class was 0.3144. These results demonstrated that students' critical thinking abilities had improved in both groups. This suggests that students who use the Smart Apps Creator application learn more effectively than those who do not in terms of their critical thinking abilities. The Mann Whitney U Test hypothesis test value at the Asymptotic Sig. A value (2-sided test) of 0.000 <0.05 indicates this. The utilization of the smart applications Creator program is found to be highly beneficial in enhancing pupils' critical thinking abilities. According to the research, students can benefit from the Smart Application Creator application by having their learning demands met and their critical thinking abilities enhanced. Teachers can use it to become more creative in creating unique learning activities and to serve as a resource for resolving various issues in learning exercises.  The contribution of this research to the future is to serve as a reference for implementing the national curriculum in Indonesia as a learning medium that can be integrated with in-depth learning.